Reframing Pandemic Preparedness: Why Positive-Pressure Exposure Control Merits Formal Public Health Evaluation - Yusaku Fujii (JMIR Public Health and Surveillance, 2026)
Abstract Powered air-purifying respirators (PAPRs) are respiratory protective devices that actively supply filtered air and maintain positive pressure in the breathing zone, thereby limiting the inward leakage of unfiltered ambient air through gaps. Their principles and technology are already established. Positive-pressure PAPRs have primarily been used by health care workers in high-risk environments. However, their potential as an individual-level infection-control measure applicable to the general public has not been formally positioned for evaluation within the context of pandemic preparedness. This viewpoint aims to demonstrate the rationale for and need to position exposure control using positive-pressure PAPRs designed for the general public as a subject of systematic public health evaluation. Unlike existing measures that depend primarily on behavioral change, spatial separation, or acquisition of immunity, this intervention directly reduces aerosol inhalation exposure in an individual’s breathing zone—the physical process that precedes airborne infection. Existing engineering studies increasingly make it possible to consider a public-oriented positive-pressure PAPR not merely as an idea but as a concrete intervention model with the potential for manufacture and implementation. However, the extent to which engineering measures of aerosol protection translate into individual-level prevention of infection and population-level infection control under real-world conditions must be established empirically. Individual-level preventive effectiveness, population-level infection-control effectiveness, engineering performance, feasibility of implementation, sustained use, social acceptability, cost, and equity must therefore be evaluated comprehensively by integrating medical and engineering assessments within a public health framework. This article does not advocate the immediate introduction of positive-pressure PAPRs for the general public. Rather, it identifies an institutional gap: established principles and technologies have not been incorporated into formal public health evaluation as a population-level infection-control measure. Evaluating positive-pressure exposure control for the general public is necessary to determine whether it could broaden policy options in future respiratory infectious disease pandemics and reduce excessive reliance on measures with major societal consequences.